منهج الإمام ابن حزم في دراسة مختلف حديث من خلال كتابه حجة الوداع" - بكار, عبد الكريم (University of Eloued-جامعة الوادي, 2016)
تناولت في هذه الرسالة منهج الإمام ابن حزم في د ا رسة مختلف الحدیث من خلال كتابه "حجة الوداع"؛ وقد اشتملت هذه الد ا رسة على مقدمة وثلاثة فصول وخاتمة. وقد بینت أن الإمام ابن حزم –رحمه الله- قد حاول جاهدا نفي التعارض الحقیقي بین الأحادیث النبویة، معتمدا في ذلك على مسالك دفع التعارض في علم مختلف الحدیث، والتي تتمثل في: الجمع والنسخ والترجیح، كما بینت أنه قد توقف في مسألة حدیثیة واحدة. وقد ذكرت أقواله في دفع التعارض، وذكرت أیضا قواعد عامة في علم مختلف الحدیث وغیره، انتهجها الإمام ابن حزم نتیجة تأثره بالمنهج الظاهري الذي تبناه؛ والذي یقوم هذا الأخیر عنده على ثلاثة أصول، وهي: النص والإجماع والدلیل. Abstract In this research paper, I have dealt with the approach of Imam Ibn Hazm in his studies of Mukhtalif Alhadith (Controversial Hadiths) through his book " Hajjat Alwada" (The prophet's farewell pilgrimage). This dissertation consists of an introduction, three chapters, and a conclusion. I have also showed that Imam Ibn Hazm tried to deny the real controversy among the hadiths depending on ways of conflicts in the studies of Mukhtalif Alhadith which are: collecting, copying, and preferring, as I have showed that he stopped at one issue of Hadith. Moreover, I have mentioned his sayings in avoiding conflicts and general rules in the studies of Mukhtalif Alhadith which Ibn Hazm followed for that he was affected by the approach he adopted, disambiguation (Zahirya) which depends on three principles: the script, the consensus, and the proof.
مذكرة